Changes in the soluble bone proteome of reared white seabream (Diplodus sargus) with skeletal deformities - Silva, Tomé S. (2014)
One of the main constrains for commercial aquaculture production of white seabream (Diplodus sargus) is the high incidence of skeletal malformations in reared fish. The purpose of this study was to obtain a better understanding of the mechanisms involved in the development of these types of skeletal malformations by comparative proteomic analysis of the vertebral column of normal and deformed fish using 2DE for protein separation and MS for protein identification. We observed a 3.2 and 3.4-fold increase in the expression of two tropomyosin isoforms, one of which (tropomyosin-4) is essential for the motility and polarization cycles of osteoclasts. Furthermore, a 1.6, 1.7 and 1.8-fold increase in three parvalbumin spots was detected, suggesting a cellular response to increased intracellular Ca2+ levels. These results can be interpreted as signs of increased cellular activity in the bone of white seabream with skeletal deformities coupled to a higher degree of calcium mobilization, which elicits further studies into the use of these proteins as indicators of skeletal metabolic state.